Molecular Characterization and Gene Expression of MHC II DRB3 Gene Associated with Subclinical Mastitis in Goats - de Guia, Arren Christian Mendoza (Archives of Veterinary Science, 2024)
The Major Histocompatibility Complex (MHC) genes have a vital role in the immune response of vertebrates by encoding molecules involved in self/non-self-discrimination and antigen presentation. This study focused on the MHC II DRB3 gene in goats, specifically comparing its nucleotide and amino acid sequences with those of other ruminant species. Four different goat breeds (Native, Upgraded, Anglo-Nubian, and Saanen) were analyzed, and their MHC II DRB3 sequences were aligned with sequences from NCBI GenBank. The nucleotide sequences exhibited high similarity between the different goat breeds and other ruminant species, indicating a conserved structure across mammalian species. Results from sequence comparisons revealed varying degrees of similarity between goat MHC II DRB3 sequences and those of Capra hircus, Ovis aries, Bos taurus, Bos grunniens, and Bubalus bubalis. Phylogenetic analysis further supported the close relationship between goats and other ruminants. Functional domain analysis identified conserved regions in the MHC II DRB3 gene across different breeds of goats and other ruminants. Moreover, polymorphism analysis using the HaeIII restriction enzyme highlighted genetic variability within the MHC II DRB3 gene in goats. This study enhances our understanding of the MHC II DRB3 gene in goats, its similarities to other ruminant species, and its potential role in immune responsiveness.